Study of the Coupled Quantum Electrodynamics System Including the Interaction with Phonons (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, we presented about the study of the coupled quantum electrodynamics system including the interaction with phonons. The energy spectrum is periodic in flux and consequently, the persistent current (PC) which is the change in ground state (GS) energy with respect to the magnetic flux is also periodic in flux. Actually, the AB effect illustrates the physicality of electromagnetic potentials φ and A.